The Importance of Being Quasi-Democratic - the Domestication Of International Human Rights in American and Arab Politics - Mednicoff, David (Victoria University of Wellington Law Review, 2007)
The paper builds on a comparative treatment of the politics of contestation and incorporation of human rights law in the United States, Morocco and Tunisia to highlight the salience of international law's democratic legitimacy problems of popular representation and mobilization. The author shows that Morocco enjoyed the most sustained and broadest recent mobilisation of these cases in the domestic extension of international human rights norms. This finding suggests four conclusions. First, democratic legitimacy problems for international law are similar across more and less democratic regime types. Second, the democratic legitimacy problem allows states to use populist appeals to justify their internal deviations from international legal norms. Third, international human rights norms stand the best possibility of mitigating these legitimacy concerns and permeating domestic practice when they have a basis in a pattern of contestation that engages more than a narrow elite, and which might therefore be called quasidemocratic. Fourth, these points demonstrate the imperative of comparing the political processes for the domestic incorporation of international law across different spaces and regime types.